Peluang dan Tantangan Interprofessional Education Di Masa Pandemi Covid-19 - Afridah, Wiwik; Fitriyah, Fifi Khoirul; Puspitasari, Silvi; Wijaya, Satria; Wikurendra, Edza Aria (TEKNOLOGI MEDIS DAN JURNAL KESEHATAN UMUM, 2021)
Health professionals are required to be ready to face challenges in the health sector (triple burden) caused by infectious diseases, degenerative diseases and emerging diseases such as Covid- 19 which is currently a pandemic. Health academics have a role to provide education and training for students with team-based service competencies. The research objective was to identify opportunities and challenges for interprofessional education (IPE) in the practical experiences of health faculty students. Collect data using a questionnaire and analyzed it descriptively. The results of the measurement of knowledge show that 73% of respondents understand IPE, 94.6% of respondents understand about working with other professions through IPE. 97.0% of respondents understand IPE to train the confidence of prospective health workers. 88.0% of respondents understand IPE to provide joint services with different professions. While the measurement results obtained 92.8% of respondents agreed to the application of IPE in learning at the Faculty of Health, choosing to agree that prospective health workers must study and practice directly for 98.8.0% by paying attention to 4 IPE factors (ethics, roles/responsibilities, interpersonal communication and teamwork, and 98.8% of respondents agreed that health services could be provided optimally if they were able to understand and appreciate the competence of each health profession, while the measurement results of IPE skills were obtained 97.0% of respondents agreed that when studying in the laboratory/field must respect different friends, 98.8% of respondents agree that students who try to be good listeners, and 56.3% of respondents who choose not to wait for orders, and 83.8% of respondents who are tasked with carrying out the correct task. It is felt that 46.7% find it difficult to use creativity when carrying out tasks when they have to work with other professions.